2014
DOI: 10.1089/scd.2013.0370
|View full text |Cite
|
Sign up to set email alerts
|

Cited2 Is Required for the Maintenance of Glycolytic Metabolism in Adult Hematopoietic Stem Cells

Abstract: Mammalian adult hematopoietic stem cells (HSCs) reside in the hypoxic bone marrow microenvironment and display a distinct metabolic phenotype compared with their progenitors. It has been proposed that HSCs generate energy mainly through anaerobic glycolysis in a pyruvate dehydrogenase kinase (Pdk)-dependent manner. Cited2 is an essential regulator for HSC quiescence, apoptosis, and function. Herein, we show that conditional deletion of Cited2 in murine HSCs results in elevated levels of reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In addition, our results showed that 2ME2 downregulated CITED2 mRNA expression, which plays a critical role in HSC metabolic regulation. 25 Suppression of CITED2 may increase apoptosis and impaire leukemia stem cell function. However, the details of the mechanism remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results showed that 2ME2 downregulated CITED2 mRNA expression, which plays a critical role in HSC metabolic regulation. 25 Suppression of CITED2 may increase apoptosis and impaire leukemia stem cell function. However, the details of the mechanism remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…CITED2, a hypoxia-and growth factorinduced transcription factor, is a negative regulatory factor to HIF-1a that acts to disrupt the interaction between HIF-1a and p300. 15 However, it has been reported that CITED2 expression has a functional role in AML maintence, 24 attenuation glycolytic metabolism, and elevation of mitochondrial activity, 25 similar to HIF-1a. Although CITED2 and HIF-1 are competitive in the regulation of hypoxia, they have similar functions in the maintenance of HSCs.…”
Section: Me2 Downregulated Expression Of Hif-1a Target Genes At the mentioning
confidence: 99%
“…For example, MEIS1 regulates both glycolysis and the oxidative stress response by activation of Hif1a transcription in HSCs 30 . Moreover, the homeobox protein CBP/p300-interacting transactivator 2 (CITED2) was found to be essential for the maintenance of HSC quiescence, in part by transcriptionally activating Hif1a , thereby increasing HIF activity 4951 .…”
Section: Glycolysis and The Hypoxic Nichementioning
confidence: 99%
“…Similar to ESCs, HSCs also contain relatively immature mitochondria, suggesting that HSCs contain mitochondria with low levels of activity. This is supported by a lower respiratory rate and a low mitochondrial membrane potential when compared with downstream progenitors (Du et al, 2014;Simsek et al, 2010). The difference in mitochondrial membrane potential between ESCs and HSCs may represent the proliferative and 'primed to differentiate' nature of ESCs, in contrast to HSCs (which are mostly quiescent).…”
Section: Mitochondrial Ros In Stem Cellsmentioning
confidence: 99%